2010
DOI: 10.1002/mds.23410
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Parkinsonism after accidental oral intake of mancozeb

Abstract: Mancozeb is a ethylene-bis-dithiocarbamate (EBDC) fungicide that contains zinc and manganese. 1 In humans, chronic EBDC inhalation has been associated with neurocognitive impairment and parkinsonism 2 while acute intoxication elicit reversible headache, dizziness, and seizures in a few cases, all of which were rapidly reversible. 3 We report a case of severe and reversible parkinsonism in a man after the accidental oral ingestion of mancozeb.A 55-year-old man with history of alcohol abuse was admitted with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…It is widely utilized for the control of a wide range of diseases in agricultural, horticultural, and ornamental crops. Several studies have shown that exposure to MZB can cause complications, including neurotoxicity (Bailey et al, 2016;Domico et al, 2006;Erro et al, 2011), carcinogenicity (Belpoggi et al, 2002), genotoxicity (Srivastava et al, 2012(Srivastava et al, , 2016, and reproductive toxicity (Bindali and Kaliwal, 2002;Iorio et al, 2015;Joshi et al, 2005;Kackar et al, 1997;Runkle et al, 2017;Girish and Reddy, 2018), which might lead to various degrees of infertility.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely utilized for the control of a wide range of diseases in agricultural, horticultural, and ornamental crops. Several studies have shown that exposure to MZB can cause complications, including neurotoxicity (Bailey et al, 2016;Domico et al, 2006;Erro et al, 2011), carcinogenicity (Belpoggi et al, 2002), genotoxicity (Srivastava et al, 2012(Srivastava et al, , 2016, and reproductive toxicity (Bindali and Kaliwal, 2002;Iorio et al, 2015;Joshi et al, 2005;Kackar et al, 1997;Runkle et al, 2017;Girish and Reddy, 2018), which might lead to various degrees of infertility.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, hydrogen peroxide, which was greatly increased following MZ-treatment, is a well-documented signaling molecule, activating both pro- and anti-survival pathways in cells (Gough and Cotter, 2011; Sies, 2014). Although reports of toxicity resulting from acute MZ exposure of humans generally leads to signs and symptoms associated with the nervous system (Erro et al, 2011; Israeli et al, 1983a, b), others have reported immunomodulatory effects (Corsini et al, 2005; Corsini et al, 2006), neural tube defects (Nordby et al, 2005), and contact dermatitis (Higo et al, 1996; Koch, 1996). In many cases, no mechanism of action is provided.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Documented cases of movement abnormalities attributed to neurotoxicity following acute exposure to commercially available maneb or mancozeb formulations have been reported for decades (Colosio et al, 1996; Erro et al, 2011; Israeli et al, 1983a, b). Recognition of the potential toxicity of MZ and maneb led to studies involving the active ingredient.…”
Section: 0 Introductionmentioning
confidence: 99%